2020
DOI: 10.3390/foods9111587
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analysis of the Effectiveness of High, Medium, and Low Voltage Electrical Stimulation on the Meat Quality of Small Ruminants

Abstract: The current study is a meta-analysis of the effects of electrical stimulation (ES, n = 28 papers) with different voltages combined with different ageing periods (0–3, 4–7, and 8–14 days) on the meat quality of small ruminants. A comprehensive search for published studies on meat quality of small ruminants investigating the application of low, medium, and high voltage electrical stimulation, was performed using Google Scholar, ScienceDirect, PubMed, and Scopus databases. Forest plots, funnel plots, and other st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 66 publications
0
11
0
Order By: Relevance
“…Furthermore, MA allows us to explore the heterogeneity sources among the diverse studies, which helps to obtain additional information about the factors contributing to the variability of the observed outcomes in response to a specific treatment [ 28 ]. MA has been frequently used in biomedical and clinical research, but its use in research related to secondary plant metabolites and meat science is still limited [ 29 ]. The objective of this meta-analysis was to evaluate the effect of dietary supplementation with tannins on productive performance, carcass characteristics, meat quality and oxidative stability, and antioxidant status of sheep blood plasma.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, MA allows us to explore the heterogeneity sources among the diverse studies, which helps to obtain additional information about the factors contributing to the variability of the observed outcomes in response to a specific treatment [ 28 ]. MA has been frequently used in biomedical and clinical research, but its use in research related to secondary plant metabolites and meat science is still limited [ 29 ]. The objective of this meta-analysis was to evaluate the effect of dietary supplementation with tannins on productive performance, carcass characteristics, meat quality and oxidative stability, and antioxidant status of sheep blood plasma.…”
Section: Introductionmentioning
confidence: 99%
“…Other methods to improve beef tenderness (including muscle proteins digestibility) revolve around post-slaughter interventions using physical methods capable of manipulating the muscular, cellular or protein structure of meat (Bekhit et al, 2014;Warner et al, 2017;Bhat et al, 2021). Among these, the most studied emerging methods include high hydrostatic pressure (HPP), pulse electric fields (PEF), ultrasound (US) and hydrodynamic shockwaves (HSW), although others such as electrical stimulation can also be effective (for review: Hwang et al, 2003;Abhijith et al, 2020). Bolumar et al (2021) recently reviewed in detail the mechanisms of action of HPP based on the pressure applied, ranging from 100 to 900 MPa.…”
Section: Physical Intervention Methods To Improve the Texture Of Fres...mentioning
confidence: 99%
“…Strategies for preserving color of camel meat were the application of post mortem low voltage ES. Abhijith et al (2020) reported that meat from electrically stimulated carcasses, have a brighter red color than meat from -non-stimulated carcasses. Using appropriate packaging and cold storage conditions (vacuum, modified atmosphere packaging (MAP) and active packaging) can play a major role in color enhancement of meat during storage (Nerin et al 2006;Camo et al 2011;Lammi et al 2018;Ait Ouahioune et al 2022a).…”
Section: Colormentioning
confidence: 99%